Promising Mediterranean Natural Oil Based Formulation to Enhance Beard Growth and Visual Performance through In Vitro and In Vivo Studies - Zahratunnisa, Hani; Pratiwi, Delfianti; Sonjaya, Ridwan (Pandawa Institute, 2025)
A well-groomed beard allows men to look distinguished as well as boosts self-confidence and self-expression. Many chemical or natural agents are used in male grooming products to improve the growth, health and quality of a man's beard. This study aimed to evaluate the effect of various natural oils in beard oil formulation on beard growth and nourishment. High-antioxidant natural oils including olive, jojoba, apricot, argan, macadamia, soybean, and avocado oils were incorporated in a beard grooming formulation to keep the beard hydrated and hydrophobic. A microbial inhibition test was conducted to assess its ability to prevent microbial growth on the beard. A total of 39 men (aged 20–29 years) participated and they had their beards shaved and underwent a washout period for 14 days without using any beard product. After this period, baseline measurements of the beard were taken before shaving it again, with assessments including length, density, and thickness using Phototrichogram and Caselite Imaging, along with trichologist evaluation and self-assessments. The subjects used the product once a day and the improvement was measured after 2 and 4 weeks. Results indicate that the beard oil formulation significantly improved beard growth rate at W2 (12.9%, p < 0.0001) and W4 (24.30%, p < 0.0001) compared to baseline. It also increases beard density at W2 (21.93% p < 0.0001) and W4 (48.43%, p < 0.0001), and improved beard thickness at W2 (9.17%, p < 0.0001) and W4 (18.34%, p < 0.0001). According to the subject self-assessment and trichologist evaluation, the product significantly improved the overall beard’s look and growth, and reduced beard roughness and itchiness. These oils also impart antibacterial activity to inhibit P. acnes proliferation. Based on this study, a formulation containing natural antioxidant oils is effective in promoting growth and preserving health by providing nourishment to the beard.